2020
DOI: 10.2174/1389450121999201013151300
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Renal Diseases: An Update

Abstract: Background: It becomes increasingly evident that the SARS-CoV-2 infection is not limited to the respiratory system. In addition to being a target of the virus, the kidney also seems to have substantial influence on the outcomes of the disease. Methods: Data was obtained by a comprehensive and non-systematic search in the PubMed, Cochrane, Scopus and SciELO databases, using mainly the terms “SARS-CoV-2”, “COVID-19”, “chronic kidney disease”, “renal transplantation”, acute kidney injury” and “renal dysfunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 111 publications
2
12
0
Order By: Relevance
“…The overall mortality of SARS-CoV-2 infection in Italy was 11.6%; a worse outcome is reported in patients with chronic diseases and cardiovascular comorbidity [ 28 ]. Consistent with previous reports [ 24 , 25 ], our population showed an elevated death rate (22.2% in patients with decompensated renal failure, 38.0% in dialysis patients, and 31.2% in transplant recipients), confirming the fragility of chronic nephropathic patients, in spite of the timely therapy against COVID-19 given in most of the cases and the reduction of immunosuppression in transplanted patients. Sadly, the work suffers from the heterogeneity of therapeutic intervention for COVID-19, mainly related to the period in which the study was conducted, the early stages of the pandemic outbreak in Italy, when a reference treatment scheme was not well defined yet.…”
Section: Discussion/conclusionsupporting
confidence: 92%
See 1 more Smart Citation
“…The overall mortality of SARS-CoV-2 infection in Italy was 11.6%; a worse outcome is reported in patients with chronic diseases and cardiovascular comorbidity [ 28 ]. Consistent with previous reports [ 24 , 25 ], our population showed an elevated death rate (22.2% in patients with decompensated renal failure, 38.0% in dialysis patients, and 31.2% in transplant recipients), confirming the fragility of chronic nephropathic patients, in spite of the timely therapy against COVID-19 given in most of the cases and the reduction of immunosuppression in transplanted patients. Sadly, the work suffers from the heterogeneity of therapeutic intervention for COVID-19, mainly related to the period in which the study was conducted, the early stages of the pandemic outbreak in Italy, when a reference treatment scheme was not well defined yet.…”
Section: Discussion/conclusionsupporting
confidence: 92%
“…SARS-CoV-2 infection is having a tremendous impact on national health systems worldwide. Our data confirm the increased susceptibility to COVID-19 of patients with advanced-stage renal failure [20], under chronic dialysis therapy [21,22] and kidney transplant recipients [23] compared to the general population, as previously reported in Italy and other industrialized countries [8,24,25].…”
Section: Discussion/conclusionsupporting
confidence: 91%
“…Renal transplant patients with COVID-19 age nearly 60, and two-third of them are males. Comorbidities reflect patients' age (diabetes, hypertension, cardiovascular and pulmonary diseases) and are frequently serious being transplanted subjects under immunosuppressive therapy to prevent rejection [50,[62][63][64][82][83][84][85]; this frequently leads COVID-19 toward a severe course [85].…”
Section: Covid-19 In Kidney Transplant Patientsmentioning
confidence: 99%
“…42 An exacerbated systemic inflammatory response and the massive release of IL-1, IL-2, IL-7, G-CSF, IP-10, MCP-1, MIP-1A, and TNFα was observed in severe COVID-19 cases. 43 Data coming from the COVID-19 pandemics showed that people with pre-existing conditions such as chronic pulmonary diseases, 44 cardiovascular diseases (CVD), 45 renal diseases, 46 and metabolic syndromes 47,48 are at higher risk of severe disease and mortality when infected. These metabolic diseases are characterized by increased levels of proinflammatory cytokines.…”
Section: Beneficial Outcomes Of Helminth and Covid-19 Co-infectionsmentioning
confidence: 99%